P regulatory products repress in vivo the P promoter activity in P-lacZ fusion genes. - Lemaitre, B (1991)
The transposition of P elements in Drosophila melanogaster is regulated by products encoded by the P elements themselves. The molecular mechanisms of this regulation are complex and still unclear. We have assayed in vivo the effects of P regulatory products on the P promoter itself by using P-lacZ fusion genes. We have found that all the P-lacZ insertions are repressed in a P background. This repression occurs in all the tissues observed and at all the developmental stages. The amount of transcripts specific for P-lacZ is substantially reduced in a P background. These results suggest that P trans-acting products can exert a direct repression on the P promoter transcription.